La calidad del servicio educativo y de la atención de los centros infantiles del buen vivir, perspectivas y expectativas de los padres de familia :estudio de caso en el CIBV “Estrellitas Mágicas” del barrio Puntiachil, parroquia: Cayambe, cantón Cayambe, Provincia de Pichincha. - Monteros Cartagena, Lidia Jhomayra (2015)
This research work was conducted in the CIBV “Magic Estrellitas” neighborhood Puntiachil Region Cayambe, Cayambe parish; This was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze quality of education and infant care centers for Good Living from the perspectives and expectations of parents; taking into account that early childhood is considered the primary stage in the life of human beings, where the development of skills and abilities is enhanced. For this we have taken into account the various theories of development proposed by several authors who have presented their research, among the highlights are: Piaget, Vygotsky, Ausubel, Dewey, Montessori. Based on this research the development of early childhood is also addressed from the cultural, spiritual and ancestral rescuing communityvalues. In this work emphasis was placed on the influence of family and parental opinion about the quality of service and attention that children’s centers provide good living children of the community.